Panggilan Tuhan Untuk Bertobat (Yoel 2:1-4) - Pinondang Jetli Simanjuntak; Feri dicky siregae (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
God's call to repentance is a theme found in the book of the prophet Joel chapter 2 verses 1-4. In this text, Joel proclaims God's call to His people to return to Him with sincerity of heart. This call carries with it the threat of punishment for disobedience, but also with the promise of grace and restoration for those who repent. This article explores the meaning and relevance of God's call to repentance in the context of today's spiritual and social life.